The SLOW GROWTH3 Pentatricopeptide Repeat Protein Is Required for the Splicing of Mitochondrial NADH Dehydrogenase Subunit7 Intron 2 in Arabidopsis. Issue 2 (17th April 2015) - Hsieh, Wei-Yu; Liao, Jo-Chien; Chang, Chiung-Yun; Harrison, Thomas; Boucher, Christina; Hsieh, Ming-Hsiun
Abstract : Incomplete splicing of a mitochondrial gene affects plant growth and development. Abstract: Mitochondria play an important role in maintaining metabolic and energy homeostasis in the cell. In plants, impairment in mitochondrial functions usually has detrimental effects on growth and development. To study genes that are important for plant growth, we have isolated a collection of slow growth ( slo ) mutants in Arabidopsis ( Arabidopsis thaliana ). One of the slo mutants, slo3, has a significant reduction in mitochondrial complex I activity. The slo3 mutant has a four-nucleotide deletion in At3g61360 that encodes a pentatricopeptide repeat (PPR) protein. The SLO3 protein contains nine classic PPR domains belonging to the P subfamily. The small deletion in the slo3 mutant changes the reading frame and creates a premature stop codon in the first PPR domain. We demonstrated that the SLO3-GFP is localized to the mitochondrion. Further analysis of mitochondrial RNA metabolism revealed that the slo3 mutant was defective in splicing of NADH dehydrogenase subunit7 ( nad7 ) intron 2. This specific splicing defect led to a dramatic reduction in complex I activity in the mutant as revealed by blue native gel analysis. Complementation of slo3 by 35S:SLO3 or 35S:SLO3-GFP restored the splicing of nad7 intron 2, the complex I activity, and the growth defects of the mutant. Together, these results indicate that the SLO3 PPR protein is a splicing factor of nad7 intron 2 in Arabidopsis mitochondria.